Immunoblot assay using excreted-secreted antigens of Trypanosoma cruzi in serodiagnosis of congenital, acute, and chronic Chagas' disease. - Umezawa, E S (1996)
Immunoblotting with trypomastigote excreted-secreted antigens (TESA blot) of Trypanosoma cruzi was evaluated as a method for diagnosis of chronic and acute phases as well as congenital (in newborn children) Chagas' disease. Serum samples from acute-phase and congenital infections were considered to be positive when they reacted with ladder-like bands of 130- to 200-kDa antigens, recognized by immunoglobulin M (IgM) and IgG antibodies, while IgG from chronic-phase sera recognized a broad band antigen of 150 to 160 kDa. Nonchagasic sera were not reactive to these antigens. The study was carried out on 512 patients, 111 of whom were nonchagasic but included cases of leishmaniasis or other pathologies, and 401 chagasic patients. The latter group comprised 361 chronic cases, 36 acute cases, and 4 congenital cases in newborn children. Among the chronic cases, 256 were from areas in which T. cruzi is endemic but which differed widely in the pathogenic expression of T. cruzi infection and in parasitemia levels. These patients at the same time showed a broad range of low, medium, and high reactivity to conventional enzyme-linked immunosorbent assays and indirect immunofluorescence serotests for Chagas' disease. For these reasons they may better represent the universe of chagasic patients than would a sample of highly reactive sera obtained from chagasic patients in a single area endemic for T. cruzi. All acute and congenital cases showed positivity in the IgM and IgG TESA blots, while chronic cases were 100% positive for IgG antibodies. In nonchagasic sera, including 30 cases of visceral and muco-cutaneous leishmaniasis, the specificity index was 1.000, and no cross-reactions were observed. The TESA blot thus seems to be useful as a sensitive and specific diagnostic assay in cases of suspected acute or congenital T. cruzi infection and as a general confirmatory test for conventional Chagas' disease serology.